Flowering and Fruiting Phenology of Tree Species in Mount Papandayan Nature Reserve, West Java, Indonesia - Endah Sulistyawati; Nusa Mashita; Nuri Nurlaila Setiawan; Devi N Choesin; Pipin Suryana (Tropical Life Sciences Research, 2012)
Mount Papandayan Nature Reserve (MPNR) is an area highly rich in biodiversity, however deforestation has left a vast area urgently in need of reforestation. When reforestation is designed to restore some level of biodiversity, it is imperative that native tree species are used for planting. This research aimed to provide information on the flowering and fruiting phenology of native trees. Such information can be useful to plan seed collection and mass seedling production in the nursery. The observations were conducted each month during August 2009–July 2010 by recording flowering and fruiting trees along two survey track passing through the middle of the mixed forest of MPNR. Data gathered were used to construct a simple phenology calendar. During the study, there were 155 trees of 43 species found flowering or fruiting along the survey track. The peak time of flowering and fruiting was in July (13 species flowering and 19 species fruiting), while the lowest level was in October (1 species flowering and 3 species fruiting). According to the phenology calendar constructed, March to July were considered to be the appropriate time to collect seeds of native trees in Mount Papandayan. Mount Papandayan Nature Reserve (MPNR) merupakan kawasan yang kaya dengan biodiversiti; namun demikian natijah daripada aktiviti pembasmian hutan secara berleluasa telah mengakibatkan perlunya penanaman semula pokok di situ dijalankan dengan segera. Apabila penanaman semula direka untuk mengembalikan semula sebahagian daripada biodiversiti, adalah amat penting untuk menggunakan spesies pokok asal dalam kaedah tersebut. Kajian ini bertujuan untuk memberi informasi berkenaan pembungaan dan fenologi pokok-pokok asal. Hal ini kerana informasi sebegini berguna untuk merancang pengumpulan biji benih dan produksi serentak bijih benih di nurseri. Melalui kajian ini, pemantauan telah dijalankan setiap bulan dari Ogos 2009–Julai 2010 dengan merekodkan pokok yang berbunga dan berbuah di sepanjang dua trek survei yang merentasi laluan di tengah-tengah hutan campur MPNR. Data yang dikumpul pula digunakan untuk membina sebuah kalendar fenologi. Dalam kajian ini, 155 pokok dari 43 spesies didapati berbunga atau berbuah. Masa kemuncak berbunga dan berbuah ialah pada bulan Julai (13 spesies berbunga dan 19 spesies berbuah), manakala tahap paling rendah ialah pada bulan Oktober (1 spesies berbunga dan 3 spesies berbuah). Berpandukan kalendar fenologi yang telah dibina, tempoh antara bulan Mac hingga Julai dianggap masa paling sesuai untuk mengumpul bijih benih pokok asal di Mount Papandayan.